Supply Function Equilibrium over a Constrained Transmission Line II: Multiple Plants and Nodal Price Derivatives - Keith Ruddell (Research Institute of Industrial Economics (IFN), 2018)
Market power in electricity wholesale markets arises when generators have incentives to mark up their offers above the cost of production.I model a transmission network with a single line. I derive optimality conditions for supply functions for generators who supply energy at both ends of the line, and also for generators who hold financial derivatives on the locational prices. These financial derivatives include contracts for differences as well as fiancial transmission rights. One way that generators can manipulate prices in their favor is by inducing congestion in the network. I find that dispersed ownership and financial transmission rights are both effective ways to reduce strategic congestion of the line. I also fid that certain portfolios of contracts for differences can lead to multiple supply function equilibria.
Keywords: C62; D43; D47; L13; L94; 330; Supply function equilibrium; Electricity markets; Market power; Financial transmission rights